Synthesis and spectroscopic properties of newly tetrapyrazinoporphyrazine containing gadolinium (III) acetate - Pişkin, Mehmet; Odabaş, Zafer; Durmuş, Mahmut (Afyon Kocatepe Üniversitesi)
A new tetrakis-(2-methylpyrazino)porphyrazinato gadolinium(III) acetate complex was synthesized.Elemental analysis, Fourier-Transform Infrared, Ultraviolet-visible, and fluorescence spectroscopytechniques clarified its structure. It can dissolve very well without aggregation in both Dimethylsulfoxide and N, N-Dimethylformamide, which have high dielectric constant and high dipolemoment from polar aprotic solvent type. Its aggregation property was also investigated in dimethylsulfoxide at different concentrations, and it was determined to contain monomeric species. Inaddition, its fluorescence properties were investigated in Dimethyl sulfoxide, and the effect ofgadolinium(III) acetate metal ion as a heavy rare earth element was determined. According to thefindings in this study, it may be used as an electronic and optical material and in varioustechnological applications such as photocatalytic applications. In addition, these findings may beuseful for systems that include changes in pyrazinoporphyrazine-like forms.

Yeni tetrakis-(2-metilpirazino)porfirazinato gadolinyum(III) asetat kompleksinin sentezlenip,saflaştırılmasının ardından yapısı element analiz, Fourier-Transform Kızılötesi, Ultraviyole görünür veFloresan spektroskopi teknikleri ile karakterize edildi. Polar aprotik solvent olan ve yüksek dielektriksabitine ve yüksek dipol momente sahip olan hem Dimetil sülfoksit hem de N,N-Dimetilformamidsolventlerinde agregasyon yapmadan iyi bir şekilde çözünebilmektedir. Dimetil sülfoksitte hazırlananbelirli farklı konsantrasyon aralıklarındaki çözeltilerindeki agregasyon özelliği araştırılarak çoğunluklamonomerik türler içerdiği de belirlenmiştir. Ayrıca; dimetil sülfoksitte hazırlanan çözeltisinin floresanözellikleri incelenerek merkezinde ağır bir nadir toprak elementi olarak gadolinyum(III) asetat metaliyonunun etkisi belirlenmiştir. Tetrakis-(2-metilpirazino)porfirazinato gadolinyum(III) asetat, elektronikve optik malzeme olarak ve fotokatalitik uygulamalar gibi çeşitli teknolojik uygulama alanlarındakullanılabilir ve pirazinoporfirazin benzeri formlardaki değişiklikleri içeren sistemler için de faydalıolabilir.
Gadolinyum (III) asetat içeren yeni tetrapirazinoporfirazinin sentezi ve spektroskopik özellikleri
Keywords: Tetrapyrazinoporphyrazine; Gadolinium (III); Acetate; Synthesis; Aggregation; Spectroscopic; Tetrapirazinoporfirazin; Gadolinyum (III); Asetat; Sentez; Agregasyon; Spektroskopi